Construction contract administration: proposal for a framework for training - Abdul Rashid, Khairuddin (2009)
Typically, a construction contract is administered by a contract administrator otherwise referred to as the Superintending Officer (S.O). Under the contract the S.O is empowered to undertake the day to day administration of the contract: to act as an agent of the Employer, to issue instructions to the contractor. to act as a certifire, etc and that he must discharge his duties fairly, reasonably and above all impartially. In the course of administering the contract, the S.O is assisted by the S.O's representatives. Lessons learned from past projects and from literature showed weaknesses in construction contract administration and that the weaknesses often lead to problems notably on contractor performance, time and cost overruns and disputes between the Employer and the contractor. In an international context such weaknesses are exacerbated by differences related to the law, practice, culture,language, etc. One of the factors contributing to the weaknesses in construction contract administration that has been identified is that parties to a contract and individuals or teams appointed to administer contracts are not sufficiently trained or not having the appropriate knowledge and skills in construction contract administration. There is therefore a need to develop appropriate training programs in best practices in construction contract administration. In this paper a framework for a training program in best practices in construction contract administration is proposed. The objecive of the training progrsm is to afford Employers. Contractors, S.Os, S.Os' representatives and others associated with construction contract administration with practical guidance on best practices in construction contract administratIon. Delegates from member countries of CLECAP are invited to deliberate on this proposal.